A.M. Hanafi menggugat : kudeta Jend. Soeharto, dari Gestapu ke Supersemar : catatan pengalaman pribadi seorang eksponen Angkatan 45. - Hanafi, A. M. (Anak Marhaen), 1917- (Lile, France : Edition Montblanc, 1998)
Political events in Indonesia, the abortive 1965 coup and General Soeharto's role; account by a political exile.
Koleksi Sumbangan : Dr. Syed Husin Ali.
Keywords: Soeharto, -- 1921-2008.; Indonesia -- Politics and government -- 1950-1966.; Indonesia -- History -- Coup détat, 1965.; Indonesia -- Politics and government -- 1966-1998.